Method for producing toner for developing electrostatic images, and toner for developing electrostatic images

JP7631950B2Active Publication Date: 2025-02-19FUJIFILM BUSINESS INNOVATION CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021047973
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-22
Publication Date
2025-02-19
Estimated Expiration
2041-03-22

AI Technical Summary

Benefits of technology

【0007】 <1>に係る発明によれば、凝集工程前及び凝集工程中において、高分子分散剤を、分散液に添加しないか、又は、得られるトナー粒子の全質量に対して、0.01質量%未満若しくは1.3質量%超の量で分散液に添加する場合に比べ、製造時における粗大粉の発生が少なく、高温高湿度環境下での帯電性に優れる静電荷像現像用トナーの製造方法が提供される。 <2>に係る発明によれば、高分子分散剤の代わりに分散剤としてアルキルベンゼンスルホン酸ナトリウムを使用した場合に比べ、製造時における粗大粉の発生がより少なく、高温高湿度環境下での帯電性により優れる静電荷像現像用トナーの製造方法が提供される。 <3>に係る発明によれば、前記高分子分散剤が、α-オレフィン-マレイン酸共重合体の塩、又は、スチレン-マレイン酸共重合体の塩である場合に比べ、製造時における粗大粉の発生がより少ない静電荷像現像用トナーの製造方法が提供される。 <4>に係る発明によれば、前記凝集工程前乃至前記凝集工程中において、前記高分子分散剤を、得られるトナー粒子の全質量に対して、0.03質量%未満の量で前記分散液に添加する場合に比べ、製造時における粗大粉の発生がより少なく、高温高湿度環境下での帯電性により優れる静電荷像現像用トナーの製造方法が提供される。 <5>に係る発明によれば、前記凝集工程前乃至前記凝集工程中において、前記高分子分散剤を、得られるトナー粒子の全質量に対して、0.05質量%未満又は1.0質量%超の量で前記分散液に添加する場合に比べ、製造時における粗大粉の発生がより少なく、高温高湿度環境下での帯電性により優れる静電荷像現像用トナーの製造方法が提供される。 <6>に係る発明によれば、前記凝集工程において、前記分散液の固形分濃度が、11質量%未満又は20質量%超である場合に比べ、製造時における粗大粉の発生がより少なく、高温高湿度環境下での帯電性により優れる静電荷像現像用トナーの製造方法が提供される。 <7>に係る発明によれば、前記高分子分散剤を水溶液にせず添加する場合に比べ、製造時における粗大粉の発生がより少なく、高温高湿度環境下での帯電性により優れる静電荷像現像用トナーの製造方法が提供される。 <8>に係る発明によれば、前記凝集工程前乃至前記凝集工程中において、前記高分子分散剤を、前記高分子分散剤の1質量%未満又は40質量%超の水溶液として添加する場合に比べ、製造時における粗大粉の発生がより少なく、高温高湿度環境下での帯電性により優れる静電荷像現像用トナーの製造方法が提供される。 <9>に係る発明によれば、凝集工程前及び凝集工程中において、高分子分散剤を、分散液に添加しないか、又は、得られるトナー粒子の全質量に対して、0.01質量%未満若しくは1.3質量%超の量で分散液に添加する場合に比べ、製造時における粗大粉の発生が少なく、高温高湿度環境下での帯電性に優れる静電荷像現像用トナーが提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631950000002
    Figure 0007631950000002
  • Figure 0007631950000003
    Figure 0007631950000003
  • Figure 0007631950000001
    Figure 0007631950000001
Patent Text Reader

Abstract

To provide a method for manufacturing a toner for electrostatic charge image development which generates less coarse powder at the time of manufacture, and is excellent in charging property under a high temperature and high humidity environment.SOLUTION: A method for manufacturing toner for electrostatic charge image development includes: an aggregation step of aggregating at least binder resin particles and release agent particles contained in a dispersion liquid to form aggregated particles; a fusion step of heating and fusing the aggregated particles to form fused particles; and a cleaning step of filtering and cleaning the fused particles to obtain toner particles. Before and during the aggregation step, 0.01 mass% or more and 1.3 mass% or less of a polymer dispersant with respect to the total mass of the obtained toner particles is added to the dispersion liquid.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a toner for developing electrostatic images, and a toner for developing electrostatic images. [Background technology]

[0002] Methods for visualizing image information, such as electrophotography, are currently used in various fields. In electrophotography, an electrostatic image is formed as image information on the surface of an image carrier by charging and forming an electrostatic image. Then, a toner image is formed on the surface of the image carrier by a developer containing a toner, and the toner image is transferred to a recording medium, and then fixed to the recording medium. Through these steps, the image information is visualized as an image.

[0003] For example, Patent Document 1 discloses a method for producing a toner for developing electrostatic images, which includes at least an aggregation step of aggregating particles while stirring a dispersion liquid containing primary polymer particles and colorant particles to obtain particle aggregates, and an aging step of fusing the particle aggregates at a temperature higher than the glass transition temperature of the primary polymer particles, characterized in that in the aging step, the temperature is increased while a dispersant is added. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-304874 A Summary of the Invention [Problem to be solved by the invention]

[0005] The object of the present invention is to provide a method for producing a toner for developing electrostatic images, which generates less coarse powder during production and has excellent charging properties in a high-temperature, high-humidity environment (28°C, 85% RH) compared to when a polymer dispersant is not added to the dispersion before or during the aggregation step, or is added to the dispersion in an amount of less than 0.01% by mass or more than 1.3% by mass relative to the total mass of the obtained toner particles. [Means for solving the problem]

[0006] Means for solving the above problems include the following aspects. <1> A method for producing a toner for developing electrostatic images, comprising: an aggregation step of aggregating at least binder resin particles and release agent particles contained in a dispersion liquid to form aggregated particles; a fusion step of heating and fusing the aggregated particles to form fused particles; and a washing step of filtering and washing the fused particles to obtain toner particles, wherein a polymer dispersant is added to the dispersion liquid before or during the aggregation step in an amount of 0.01% by mass or more and 1.3% by mass or less based on the total mass of the toner particles to be obtained. <2> The polymer dispersant is at least one compound selected from the group consisting of formalin condensate sulfonate, a salt of an α-olefin-maleic acid copolymer, and a salt of a styrene-maleic acid copolymer. <1> 2. A method for producing the toner for developing electrostatic images according to claim 1 . <3> The polymer dispersant is a formalin condensate sulfonate. <2> 2. A method for producing the toner for developing electrostatic images according to claim 1 . <4> Before or during the aggregation step, the polymer dispersant is added to the dispersion in an amount of 0.03% by mass or more and 1.3% by mass or less with respect to the total mass of the toner particles to be obtained. <1> ~ <3> 13. A method for producing the toner for developing electrostatic images according to claim 12. <5> Before or during the aggregation step, the polymer dispersant is added to the dispersion in an amount of 0.05% by mass or more and 1.0% by mass or less with respect to the total mass of the toner particles to be obtained. <4> 2. A method for producing the toner for developing electrostatic images according to claim 1 . <6> In the aggregating step, the solid content concentration of the dispersion is 11% by mass or more and 20% by mass or less. <1> ~ <5> 13. A method for producing the toner for developing electrostatic images according to claim 12. <7> The polymer dispersant is added as an aqueous solution of the polymer dispersant before or during the flocculation step. <1> ~ <6> 13. A method for producing the toner for developing electrostatic images according to claim 12. <8> Before or during the agglomeration step, the polymer dispersant is added as an aqueous solution containing the polymer dispersant in an amount of 1% by mass or more and 40% by mass or less. <7> 2. A method for producing the toner for developing electrostatic images according to claim 1 . <9> <1> ~ <8> 2. A toner for developing electrostatic images, which is produced by the method for producing a toner for developing electrostatic images according to claim 1. Effect of the Invention

[0007] <1> According to the invention, there is provided a method for producing a toner for developing electrostatic images, which generates less coarse powder during production and has excellent charging properties under high temperature and high humidity environments, compared to when a polymer dispersant is not added to the dispersion before or during the aggregation step, or is added to the dispersion in an amount of less than 0.01 mass % or more than 1.3 mass % relative to the total mass of the obtained toner particles. <2> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which generates less coarse powder during production and has superior charging properties under high temperature and high humidity environments, as compared to a case in which sodium alkylbenzenesulfonate is used as a dispersant instead of a polymer dispersant. <3> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which generates less coarse powder during production, as compared with the case where the polymer dispersant is a salt of an α-olefin-maleic acid copolymer or a salt of a styrene-maleic acid copolymer. <4> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which generates less coarse powder during production and has better charging properties under high temperature and high humidity environments, compared to a case in which the polymer dispersant is added to the dispersion liquid before or during the aggregation step in an amount of less than 0.03 mass % relative to the total mass of the toner particles to be obtained. <5> According to the invention, there is provided a method for producing a toner for developing electrostatic images, which generates less coarse powder during production and has better charging properties under high temperature and high humidity environments, compared to a case in which the polymer dispersant is added to the dispersion liquid before or during the aggregation step in an amount of less than 0.05 mass % or more than 1.0 mass %, relative to the total mass of the toner particles to be obtained. <6> According to the invention, there is provided a method for producing a toner for developing electrostatic images, which generates less coarse powder during production and has better charging properties under high temperature and high humidity environments, compared to when the solids concentration of the dispersion liquid is less than 11 mass % or more than 20 mass % in the aggregation step. <7> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which generates less coarse powder during production and has better charging properties under high temperature and high humidity environments, compared to when the polymer dispersant is added without being made into an aqueous solution. <8> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which generates less coarse powder during production and has better charging properties under high temperature and high humidity environments, compared to a case in which the polymer dispersant is added as an aqueous solution containing less than 1% by mass or more than 40% by mass of the polymer dispersant before or during the aggregation step. <9> According to the invention, there is provided a toner for developing electrostatic images which generates less coarse powder during production and has excellent charging properties under high temperature and high humidity environments, compared to when a polymer dispersant is not added to the dispersion before or during the aggregation step, or is added to the dispersion in an amount of less than 0.01 mass % or more than 1.3 mass % relative to the total mass of the obtained toner particles. [Brief description of the drawings]

[0008] [Figure 1]1 is a schematic configuration diagram illustrating an example of an image forming apparatus according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram illustrating an example of a process cartridge according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described in detail. In addition, in numerical ranges described in stages, the upper limit or lower limit value described in a certain numerical range may be replaced with the upper limit or lower limit value of another numerical range described in stages. In addition, in a numerical range, the upper limit or lower limit described in a certain numerical range may be replaced with a value shown in the examples. When a plurality of substances corresponding to each component are present in the composition, the amount of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified. The term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved.

[0010] (Method of manufacturing toner for developing electrostatic images) The method for producing a toner for developing electrostatic images according to the present embodiment includes an aggregation step of aggregating at least binder resin particles and release agent particles contained in a dispersion liquid to form aggregated particles, a fusion step of heating and fusing the aggregated particles to form fused particles, and a washing step of filtering and washing the fused particles to obtain toner particles, and a polymer dispersant is added to the dispersion liquid in an amount of 0.01% by mass or more and 1.3% by mass or less, based on the total mass of the toner particles to be obtained, before or during the aggregation step. The electrostatic image developing toner according to this embodiment is a toner produced by the method for producing the electrostatic image developing toner according to this embodiment.

[0011] Methods for efficiently producing toner include wet manufacturing methods such as emulsion polymerization aggregation and suspension polymerization. Among these, the emulsion polymerization aggregation method is particularly excellent for narrowing the particle size distribution of toner. In the emulsion polymerization aggregation method, coarse powder may be generated during aggregation and fusion, and it is known that a dispersant is added to suppress this. For example, Patent Document 1 discloses a method for suppressing coarse powder generated in the fusion process without affecting toner quality by adding a dispersant in the fusion process, but this may result in deterioration of charging properties. In the method for producing the toner for developing electrostatic images according to the present embodiment, it is estimated that adding a polymer dispersant to the dispersion liquid before and during the aggregation step in an amount of 0.01% by mass to 1.3% by mass based on the total mass of the toner particles to be obtained reduces the viscosity of the dispersion liquid during aggregation, improves the stirring efficiency, and suppresses the generation of coarse powder. It is also estimated that by setting the amount of polymer dispersant added within the above range, the effect of suppressing the generation of coarse powder is sufficiently obtained, and the polymer dispersant contained in the toner particles to be obtained is sufficiently removed in the washing step, suppressing the decrease in charging property under a high temperature and high humidity environment (28°C 85% RH) due to the remaining polymer dispersant.

[0012] The method for producing the toner for developing electrostatic images according to this embodiment is a method for producing toner particles by an aggregation / coalescence method. Each step will be described in detail below.

[0013] <Agglomeration process> The method for producing a toner for developing electrostatic images according to the present embodiment includes an aggregation step of aggregating at least binder resin particles and release agent particles contained in a dispersion liquid to form aggregated particles, and before or during the aggregation step, a polymer dispersant is added to the dispersion liquid in an amount of 0.01% by mass or more and 1.3% by mass or less with respect to the total mass of the toner particles to be obtained.

[0014] The polymer dispersant is a compound having a weight average molecular weight Mw of 1,000 or more. The polymer dispersant is preferably a water-soluble polymer dispersant from the viewpoints of suppressing coarse powder and electrostatic chargeability in a high-temperature, high-humidity environment. In this embodiment, "water-soluble" means that the target substance dissolves in water at 25°C at 0.5% by mass or more, and preferably 1% by mass or more. From the viewpoints of suppressing coarse powder formation and electrostatic chargeability in a high-temperature, high-humidity environment, the polymer dispersant preferably has at least an acid group or a salt structure thereof, more preferably has at least a sulfonic acid group, a carboxyl group, or a salt structure thereof, and particularly preferably has a sulfonic acid group or a salt structure thereof. Furthermore, from the viewpoints of suppressing coarse powder generation and electrostatic chargeability in a high-temperature, high-humidity environment, it is preferable that the polymer dispersant has a salt structure. The salt structure is preferably an alkali metal salt structure or an ammonium salt structure, and more preferably an alkali metal salt structure.

[0015] Examples of the polymer dispersant include sulfonic acid compound-formaldehyde condensates, α-olefin-maleic acid copolymers, styrene-maleic acid copolymers, poly(meth)acrylic acid, carboxymethyl cellulose, polystyrene sulfonic acid, (meth)acrylamide-(meth)acrylic acid copolymers, alginic acid, styrene-styrene sulfonic acid copolymers, styrene-(meth)acrylic acid copolymers, vinyl naphthalene-maleic acid copolymers, vinyl naphthalene-(meth)acrylic acid copolymers, vinyl naphthalene-acrylic acid copolymers, (meth)acrylic acid alkyl ester-(meth)acrylic acid copolymers, styrene-(meth)acrylic acid alkyl ester-(meth)acrylic acid copolymers, and salts thereof. Among these, from the viewpoints of suppressing coarse powder generation and electrostatic chargeability in a high-temperature, high-humidity environment, the polymer dispersant is preferably at least one compound selected from the group consisting of formalin condensate sulfonate, a salt of an α-olefin-maleic acid copolymer, and a salt of a styrene-maleic acid copolymer, more preferably a formalin condensate sulfonate, and particularly preferably a formalin condensate sulfonate alkali metal salt. The formalin condensate sulfonate is preferably a salt of an aromatic sulfonic acid compound-formalin condensate, more preferably a naphthalenesulfonate-formalin condensate, and particularly preferably a naphthalenesulfonate-alkali metal salt-formalin condensate.

[0016] The total amount of polymer dispersant added to the dispersion liquid before and during the aggregation process is 0.01% by mass or more and 1.3% by mass or less, relative to the total mass of the toner particles to be obtained. From the viewpoints of suppressing coarse powder formation and chargeability in a high-temperature, high-humidity environment, the total amount is preferably 0.03% by mass or more and 1.3% by mass or less, more preferably 0.05% by mass or more and 1.0% by mass or less, and particularly preferably 0.1% by mass or more and 0.8% by mass or less.

[0017] In the method for producing a toner for developing electrostatic images according to the present embodiment, the polymer dispersant may be added before the aggregation step, i.e., before the addition of the aggregating agent, or during the aggregation step, i.e., after the addition of the aggregating agent and while the aggregated particles are being formed. However, from the viewpoint of suppressing the generation of coarse powder, it is preferable to add the polymer dispersant before the aggregation step, i.e., before the addition of the aggregating agent.

[0018] Furthermore, before or during the aggregation process, from the viewpoints of suppressing coarse powder formation and charging properties in a high-temperature, high-humidity environment, it is preferable to add the polymer dispersant as an aqueous solution of the polymer dispersant, it is more preferable to add the polymer dispersant as an aqueous solution containing 1% by mass or more and 40% by mass or less of the polymer dispersant, and it is particularly preferable to add the polymer dispersant as an aqueous solution containing 5% by mass or more and 30% by mass or less of the polymer dispersant.

[0019] The dispersion in the aggregation step is preferably an aqueous dispersion, and more preferably an aqueous dispersion. Examples of the dispersion medium used in the dispersion liquid in the aggregation step include an aqueous medium. Examples of the aqueous medium include water such as distilled water and ion-exchanged water, alcohols, etc. These may be used alone or in combination of two or more kinds.

[0020] The dispersion liquid in the aggregation step preferably contains a surfactant other than the polymer dispersant. Examples of the surfactant include anionic surfactants such as sulfate salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. Among these, anionic surfactants and cationic surfactants are particularly preferred. The nonionic surfactants may be used in combination with anionic surfactants or cationic surfactants. The surfactant may be used alone or in combination of two or more kinds.

[0021] The volume average particle size of the binder resin particles before aggregation dispersed in the dispersion liquid is preferably 0.01 μm or more and 1 μm or less, more preferably 0.04 μm or more and 0.8 μm or less, and even more preferably 0.06 μm or more and 0.6 μm or less. The volume average particle size of the release agent particles before aggregation dispersed in the dispersion liquid is preferably from 0.01 μm to 1 μm, more preferably from 0.08 μm to 0.8 μm, and even more preferably from 0.1 μm to 0.6 μm. The volume average particle size of the resin particles and the release agent particles is measured by using a particle size distribution obtained by measurement using a laser diffraction particle size distribution measuring device (for example, LA-700 manufactured by Horiba, Ltd.), subtracting the cumulative distribution from the small particle size side for the volume of the divided particle size range (channel), and measuring the particle size at which the cumulative distribution is 50% of all particles as the volume average particle size D50v. The volume average particle sizes of particles in other dispersions are also measured in the same manner.

[0022] The dispersion liquid may further contain colorant particles to be used in the toner particles. The preferred volume average particle size of the colorant particles is the same as the preferred volume average particle size of the binder resin particles.

[0023] In the aggregation step, the solid content concentration of the dispersion liquid is preferably 5% by mass or more and 30% by mass or less, more preferably 8% by mass or more and 25% by mass or less, and particularly preferably 11% by mass or more and 20% by mass or less, from the viewpoints of dispersibility of the binder resin particles, the release agent particles, etc., suppression of coarse powder, and electrostatic chargeability under a high-temperature and high-humidity environment.

[0024] In the aggregation step, for example, an aggregating agent is added to the dispersion liquid, the pH of the mixed dispersion liquid is adjusted to be acidic (for example, a pH of 2 or more and 5 or less), and the mixed dispersion liquid is heated to a temperature of the glass transition temperature of the binder resin particles (specifically, for example, a temperature of the glass transition temperature of the binder resin particles -30°C or more and the glass transition temperature -10°C or less), and each particle dispersed in the dispersion liquid is aggregated to form aggregated particles. In the aggregation step, for example, the dispersion may be stirred with a rotary shear homogenizer, the aggregating agent may be added at room temperature (e.g., 25°C), the pH of the dispersion may be adjusted to an acidic state (e.g., pH 2 or more and 5 or less), and a dispersion stabilizer may be added as necessary, followed by the heating.

[0025] Examples of the flocculant include a surfactant having a polarity opposite to that of the polymer dispersant added to the dispersion liquid, an inorganic metal salt, and a divalent or higher metal complex. In particular, when a metal complex is used as the flocculant, the charging characteristics are improved. If necessary, an additive that forms a complex or a similar bond with the metal ions of the flocculant may be used, and a chelating agent is preferably used as this additive.

[0026] Examples of inorganic metal salts include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate, as well as inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide. The chelating agent may be a water-soluble chelating agent, such as oxycarboxylic acid (e.g., tartaric acid, citric acid, gluconic acid, etc.), iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), ethylenediaminetetraacetic acid (EDTA), etc. The amount of the flocculant added is, for example, preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, relative to 100 parts by mass of the binder resin particles.

[0027] The volume average particle size of the aggregated particles obtained in the aggregation step is not particularly limited, and can be appropriately selected depending on the volume average particle size of the desired toner particles.

[0028] The preferred embodiments of each of the components contained in the toner particles, such as the binder resin, the release agent, and the colorant, will be described below.

[0029] <Fusion process> The method for producing the toner for developing electrostatic images according to the present embodiment includes a fusing step of heating and fusing the aggregated particles to form fused particles. In the fusing step, the aggregated particle dispersion liquid in which the aggregated particles are dispersed is heated, for example, to a temperature equal to or higher than the glass transition temperature of the binder resin particles (for example, a temperature 30° C. to 50° C. higher than the glass transition temperature of the binder resin particles) and equal to or higher than the melting temperature of the release agent, to fuse and coalesce the aggregated particles to form toner particles. In the fusion step, the binder resin and the release agent are in a fused state at temperatures equal to or higher than the glass transition temperature of the binder resin particles and the melting temperature of the release agent. Thereafter, the mixture is cooled to obtain toner particles. The aspect ratio of the release agent in the toner particles can be adjusted by holding the release agent at a temperature around its freezing point for a certain period of time during cooling to cause crystal growth, or by using two or more types of release agents with different melting temperatures to promote crystal growth during cooling.

[0030] <Cleaning process> The method for producing a toner for developing an electrostatic image according to this embodiment includes a washing step of filtering and washing the fused particles to obtain toner particles. The washing in the washing step is preferably carried out with water, and from the viewpoint of chargeability, it is more preferable to carry out sufficient replacement washing with ion-exchanged water. The amount of water used in the washing is not particularly limited, but is preferably an amount that allows the polymer dispersant and the like to be sufficiently removed. The filtration in the washing step is not particularly limited, but from the viewpoint of productivity, it is preferable to carry out suction filtration, pressure filtration, or the like.

[0031] The method for producing the toner for developing electrostatic images according to this embodiment preferably includes a drying step of drying the toner particles after the cleaning step. The drying method in the drying step is not particularly limited, but from the viewpoint of productivity, it is preferable to carry out freeze drying, flash drying, fluidized drying, vibration type fluidized drying, etc.

[0032] The content of the polymer dispersant in the toner particles after the washing step, preferably after the drying step, is preferably less than 100 ppm, more preferably 50 ppm or less, and particularly preferably 10 ppm or less, from the viewpoint of chargeability under a high temperature and high humidity environment.

[0033] The method for producing the toner for developing electrostatic images according to the present embodiment preferably includes a step of externally adding an external additive to the obtained toner particles. The external addition may be carried out, for example, by using a V blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, if necessary, coarse particles of the toner may be removed using a vibration sifter, a wind sifter, etc.

[0034] <Binder resin particle dispersion liquid preparation process> The method for producing the toner for developing electrostatic images according to the present embodiment preferably includes a binder resin particle dispersion preparation step of preparing a binder resin particle dispersion. In addition to the binder resin particle dispersion liquid in which the binder resin particles are dispersed, for example, the method for producing the toner for developing electrostatic images according to the present embodiment preferably includes a step of preparing a colorant particle dispersion liquid in which colorant particles are dispersed, and a step of preparing a release agent particle dispersion liquid in which release agent particles are dispersed.

[0035] The resin particle dispersion liquid is prepared, for example, by dispersing resin particles in a dispersion medium with the aid of a surfactant.

[0036] The dispersion medium used in the resin particle dispersion liquid is, for example, an aqueous medium. Examples of the aqueous medium include water such as distilled water and ion-exchanged water, alcohols, etc. These may be used alone or in combination of two or more kinds.

[0037] Examples of the surfactant include anionic surfactants such as sulfate salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. Among these, anionic surfactants and cationic surfactants are particularly preferred. The nonionic surfactants may be used in combination with anionic surfactants or cationic surfactants. The surfactant may be used alone or in combination of two or more kinds.

[0038] In the resin particle dispersion, the resin particles are dispersed in the dispersion medium by a general dispersion method such as a rotary shear type homogenizer, a ball mill having a media, a sand mill, or a dyno mill. Depending on the type of resin particles, the resin particles may be dispersed in the dispersion medium by a phase inversion emulsification method. The phase inversion emulsification method is a method in which the resin to be dispersed is dissolved in a hydrophobic organic solvent in which the resin is soluble, a base is added to the organic continuous phase (O phase) to neutralize it, and then an aqueous medium (W phase) is added to invert the phase from W / O to O / W, thereby dispersing the resin in the aqueous medium in the form of particles.

[0039] The volume average particle size of the resin particles dispersed in the resin particle dispersion is, for example, preferably from 0.01 μm to 1 μm, more preferably from 0.08 μm to 0.8 μm, and even more preferably from 0.1 μm to 0.6 μm.

[0040] The content of the resin particles in the resin particle dispersion is preferably from 5% by mass to 50% by mass, and more preferably from 10% by mass to 40% by mass.

[0041] In the same manner as the resin particle dispersion liquid, for example, a colorant particle dispersion liquid and a release agent particle dispersion liquid are also prepared. That is, the volume average particle size, dispersion medium, dispersion method, and particle content of the particles in the resin particle dispersion liquid are the same for the colorant particles dispersed in the colorant particle dispersion liquid and the release agent particles dispersed in the release agent particle dispersion liquid.

[0042] The method for producing the toner for developing electrostatic images according to the present embodiment may further include, after the aggregation step, a step of further mixing the dispersion liquid containing the aggregated particles with a resin particle dispersion liquid in which binder resin particles are dispersed, and aggregating the aggregated particles so that the binder resin particles are further attached to the surfaces of the aggregated particles to form second aggregated particles. By passing through the step of forming the second aggregated particles, toner particles having a core-shell structure are formed.

[0043] The method for producing the toner for developing electrostatic images according to the present embodiment may include known steps other than those described above.

[0044] Each component contained in the toner for developing an electrostatic image will be described in detail below.

[0045] <Binding resin> The binder resin preferably contains an amorphous resin, and more preferably contains an amorphous resin and a crystalline resin from the viewpoints of image strength and suppression of uneven density in the obtained image. That is, in the aggregation step, it is more preferable that the binder resin particles contain an amorphous resin particle and a crystalline resin particle.

[0046] Here, the term "amorphous resin" refers to a resin that, in a thermal analysis measurement using differential scanning calorimetry (DSC), has only a stepwise endothermic change rather than a clear endothermic peak, is a solid at room temperature, and is thermoplasticized at a temperature equal to or higher than the glass transition temperature. On the other hand, a crystalline resin refers to a resin that has a clear endothermic peak rather than a stepwise change in endothermic amount in differential scanning calorimetry (DSC). Specifically, for example, a crystalline resin means a resin whose half-width of an endothermic peak is within 10°C when measured at a heating rate of 10°C / min, and an amorphous resin means a resin whose half-width exceeds 10°C or a resin in which no clear endothermic peak is observed.

[0047] The amorphous resin will be described. Examples of the amorphous resin include known amorphous resins such as amorphous polyester resin, amorphous vinyl resin (e.g., styrene acrylic resin, etc.), epoxy resin, polycarbonate resin, polyurethane resin, etc. Among these, from the viewpoint of suppressing uneven density and suppressing white spots in the obtained image, amorphous polyester resin and amorphous vinyl resin (particularly styrene acrylic resin) are preferred, and amorphous polyester resin is more preferred. In addition, it is also a preferred embodiment to use an amorphous polyester resin and a styrene-acrylic resin in combination as the amorphous resin.

[0048] The amorphous polyester resin may be, for example, a condensation polymer of a polyvalent carboxylic acid and a polyhydric alcohol. As the amorphous polyester resin, a commercially available product or a synthesized product may be used.

[0049] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). Among these, aromatic dicarboxylic acids are preferred as the polyvalent carboxylic acid. The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, and lower (e.g., carbon number 1 to 5) alkyl esters thereof. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.

[0050] Examples of polyhydric alcohols include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, aromatic diols and alicyclic diols are preferred as polyhydric alcohols, and aromatic diols are more preferred. As the polyhydric alcohol, a polyhydric alcohol having a crosslinked or branched structure of three or more may be used in combination with the diol. Examples of the polyhydric alcohol having a trihydric or higher valence include glycerin, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0051] The amorphous polyester resin is obtained by a known manufacturing method. Specifically, for example, the polymerization temperature is set to 180°C or more and 230°C or less, the reaction system is depressurized as necessary, and the reaction is carried out while removing water and alcohol generated during condensation. If the raw material monomer is not dissolved or compatible at the reaction temperature, a high-boiling point solvent may be added as a dissolution aid to dissolve it. In this case, the polycondensation reaction is carried out while distilling off the dissolution aid. If a monomer with poor compatibility is present in the copolymerization reaction, it is recommended that the monomer with poor compatibility is condensed in advance with the acid or alcohol to be polycondensed with the monomer and then polycondensed with the main component.

[0052] As the binder resin, particularly the amorphous resin, a styrene-acrylic resin can be mentioned. The styrene-acrylic resin is a copolymer obtained by copolymerizing at least a styrene-based monomer (a monomer having a styrene skeleton) and a (meth)acrylic-based monomer (a monomer having a (meth)acrylic group, preferably a monomer having a (meth)acryloxy group). The styrene-acrylic resin includes, for example, a copolymer of a styrene monomer and a (meth)acrylic acid ester monomer. The acrylic resin portion of the styrene-acrylic resin is a partial structure formed by polymerizing either an acrylic monomer or a methacrylic monomer, or both. In addition, the term "(meth)acrylic" includes both "acrylic" and "methacrylic".

[0053] Specific examples of styrene-based monomers include styrene, alkyl-substituted styrenes (e.g., α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, etc.), halogen-substituted styrenes (e.g., 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, etc.), vinylnaphthalene, etc. The styrene-based monomers may be used alone or in combination of two or more. Of these, as the styrene-based monomer, styrene is preferred from the viewpoints of ease of reaction, ease of reaction control, and availability.

[0054] Specific examples of the (meth)acrylic monomer include (meth)acrylic acid and (meth)acrylic acid esters. Examples of the (meth)acrylic acid esters include (meth)acrylic acid alkyl esters (e.g., methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tetradecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-octadecyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, isopentyl (meth)acrylate, amyl (meth)acrylate, and (meth) Examples of the (meth)acrylic acid monomer include neopentyl acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, etc.), aryl (meth)acrylate esters (e.g., phenyl (meth)acrylate, biphenyl (meth)acrylate, diphenylethyl (meth)acrylate, t-butylphenyl (meth)acrylate, terphenyl (meth)acrylate, etc.), dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, β-carboxyethyl (meth)acrylate, and (meth)acrylamide. The (meth)acrylic acid monomer may be used alone or in combination of two or more. Among these (meth)acrylic esters among the (meth)acrylic monomers, from the viewpoint of fixation, (meth)acrylic acid esters having an alkyl group having 2 to 14 carbon atoms (preferably 2 to 10 carbon atoms, more preferably 3 to 8 carbon atoms) are preferred. Of these, n-butyl (meth)acrylate is preferred, and n-butyl acrylate is particularly preferred.

[0055] The copolymerization ratio of the styrene monomer to the (meth)acrylic monomer (mass basis, styrene monomer / (meth)acrylic monomer) is not particularly limited, but is preferably 85 / 15 to 70 / 30.

[0056] The styrene-acrylic resin may have a crosslinked structure. A preferred example of the styrene-acrylic resin having a crosslinked structure is a copolymer of at least a styrene-based monomer, a (meth)acrylic acid-based monomer, and a crosslinkable monomer.

[0057] The crosslinkable monomer may, for example, be a bifunctional or higher functional crosslinking agent. Examples of bifunctional crosslinking agents include divinylbenzene, divinylnaphthalene, di(meth)acrylate compounds (e.g., diethylene glycol di(meth)acrylate, methylene bis(meth)acrylamide, decanediol diacrylate, glycidyl (meth)acrylate, etc.), polyester type di(meth)acrylate, 2-([1'-methylpropylideneamino]carboxyamino)ethyl methacrylate, etc. Examples of polyfunctional crosslinking agents include tri(meth)acrylate compounds (e.g., pentaerythritol tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, etc.), tetra(meth)acrylate compounds (e.g., pentaerythritol tetra(meth)acrylate, oligoester (meth)acrylate, etc.), 2,2-bis(4-methacryloxy, polyethoxyphenyl)propane, diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, triallyl trimellitate, diaryl chlorendate, etc. Among these, as the crosslinkable monomer, from the viewpoints of suppressing the occurrence of a decrease in image density and suppressing the occurrence of uneven image density, and of fixability, a bifunctional or higher (meth)acrylate compound is preferred, a bifunctional (meth)acrylate compound is more preferred, a bifunctional (meth)acrylate compound having an alkylene group having 6 to 20 carbon atoms is even more preferred, and a bifunctional (meth)acrylate compound having a linear alkylene group having 6 to 20 carbon atoms is particularly preferred.

[0058] The copolymerization ratio of the crosslinkable monomer to the total monomers (mass basis, crosslinkable monomer / total monomers) is not particularly limited, but is preferably 2 / 1,000 to 20 / 1,000.

[0059] The method for producing the styrene-acrylic resin is not particularly limited, and various polymerization methods (e.g., solution polymerization, precipitation polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc.) are applied. In addition, the polymerization reaction is carried out by a known operation (e.g., batchwise, semi-continuous, continuous, etc.).

[0060] The proportion of the styrene-acrylic resin in the total binder resin is preferably from 0% to 20% by mass, more preferably from 1% to 15% by mass, and even more preferably from 2% to 10% by mass.

[0061] The proportion of the amorphous resin in the total binder resin is preferably 60% by mass or more and 98% by mass or less, more preferably 65% ​​by mass or more and 95% by mass or less, and even more preferably 70% by mass or more and 90% by mass or less.

[0062] The characteristics of the amorphous resin will be described. The glass transition temperature (Tg) of the amorphous resin is preferably 50°C or higher and 80°C or lower, and more preferably 50°C or higher and 65°C or lower. The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, from the "extrapolated glass transition onset temperature" described in the method for determining glass transition temperature in JIS K 7121-1987 "Method for measuring transition temperature of plastics."

[0063] The weight average molecular weight (Mw) of the amorphous resin is preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less. The number average molecular weight (Mn) of the amorphous resin is preferably 2,000 or more and 100,000 or less. The molecular weight distribution Mw / Mn of the amorphous resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less. The weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC is performed using a Tosoh GPC HLC-8120GPC as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent. The weight average molecular weight and number average molecular weight are calculated from the measurement results using a molecular weight calibration curve created with a monodisperse polystyrene standard sample.

[0064] The crystalline resin will now be described. Examples of the crystalline resin include known crystalline resins such as crystalline polyester resins and crystalline vinyl resins (e.g., polyalkylene resins, long-chain alkyl (meth)acrylate resins, etc.). Among these, crystalline polyester resins are preferred from the viewpoint of suppressing uneven density and white spots in the resulting image.

[0065] The crystalline polyester resin may be, for example, a polycondensate of a polyvalent carboxylic acid and a polyhydric alcohol. As the crystalline polyester resin, a commercially available product or a synthesized product may be used. Since the crystalline polyester resin easily forms a crystalline structure, a polycondensation product using a straight-chain aliphatic polymerizable monomer is preferable to a polymerizable monomer having an aromatic ring.

[0066] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, and their lower (e.g., carbon number 1 to 5) alkyl esters. As the polyvalent carboxylic acid, a dicarboxylic acid having a sulfonic acid group and a dicarboxylic acid having an ethylenic double bond may be used in combination with these dicarboxylic acids. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.

[0067] Examples of polyhydric alcohols include aliphatic diols (for example, straight-chain aliphatic diols having 7 to 20 carbon atoms in the main chain). Examples of aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanedecanediol. Among these, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred as aliphatic diols. The polyhydric alcohol may be a trihydric or higher alcohol having a crosslinked or branched structure in combination with the diol. Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0068] The polyhydric alcohol may have an aliphatic diol content of 80 mol % or more, and preferably 90 mol % or more.

[0069] The melting temperature of the crystalline polyester resin is preferably 50°C or higher and 100°C or lower, more preferably 55°C or higher and 90°C or lower, and even more preferably 60°C or higher and 85°C or lower. The melting temperature of the crystalline polyester resin is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "melting peak temperature" described in the method for determining melting temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0070] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.

[0071] The crystalline polyester resin can be obtained, for example, by a known production method, like the amorphous polyester resin.

[0072] As the crystalline polyester resin, a polymer of an α,ω-linear aliphatic dicarboxylic acid and an α,ω-linear aliphatic diol is preferred from the viewpoint of easily forming a crystal structure and having good compatibility with the amorphous polyester resin, thereby improving the fixability of the image.

[0073] The α,ω-linear aliphatic dicarboxylic acid is preferably an α,ω-linear aliphatic dicarboxylic acid in which the alkylene group connecting the two carboxy groups has 3 or more and 14 or less carbon atoms, more preferably the alkylene group has 4 or more and 12 or less carbon atoms, and even more preferably the alkylene group has 6 or more and 10 or less carbon atoms. Examples of α,ω-linear aliphatic dicarboxylic acids include succinic acid, glutaric acid, adipic acid, 1,6-hexanedicarboxylic acid (commonly known as suberic acid), 1,7-heptanedicarboxylic acid (commonly known as azelaic acid), 1,8-octanedicarboxylic acid (commonly known as sebacic acid), 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid. Of these, 1,6-hexanedicarboxylic acid, 1,7-heptanedicarboxylic acid, 1,8-octanedicarboxylic acid, and 1,10-decanedicarboxylic acid are preferred. The α,ω-linear aliphatic dicarboxylic acids may be used alone or in combination of two or more kinds.

[0074] The α,ω-linear aliphatic diol is preferably an α,ω-linear aliphatic diol in which the alkylene group connecting the two hydroxy groups has 3 to 14 carbon atoms, more preferably the alkylene group has 4 to 12 carbon atoms, and further preferably the alkylene group has 6 to 10 carbon atoms. Examples of the α,ω-linear aliphatic diol include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, and 1,18-octadecanediol. Of these, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred. The α,ω-linear aliphatic diols may be used alone or in combination of two or more kinds.

[0075] As the polymer of an α,ω-linear aliphatic dicarboxylic acid and an α,ω-linear aliphatic diol, from the viewpoint of easily forming a crystal structure and having good compatibility with an amorphous polyester resin, thereby improving the fixability of an image, a polymer of at least one selected from the group consisting of 1,6-hexanedicarboxylic acid, 1,7-heptanedicarboxylic acid, 1,8-octanedicarboxylic acid, 1,9-nonanedicarboxylic acid, and 1,10-decanedicarboxylic acid and at least one selected from the group consisting of 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol is preferred, and among these, a polymer of 1,10-decanedicarboxylic acid and 1,6-hexanediol is more preferred.

[0076] The proportion of the crystalline resin in the total binder resin is preferably from 1% by mass to 20% by mass, more preferably from 2% by mass to 15% by mass, and even more preferably from 3% by mass to 10% by mass.

[0077] Other binder resins Examples of the binder resin include homopolymers of monomers such as ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.) and olefins (e.g., ethylene, propylene, butadiene, etc.), and copolymers of two or more of these monomers. Other examples of the binder resin include non-vinyl resins such as epoxy resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosin, mixtures of these with the vinyl resins, and graft polymers obtained by polymerizing vinyl monomers in the coexistence of these. These binder resins may be used alone or in combination of two or more kinds.

[0078] The content of the binder resin is preferably from 40% by mass to 95% by mass, more preferably from 50% by mass to 90% by mass, and even more preferably from 60% by mass to 85% by mass, based on the total mass of the toner particles.

[0079] -Release agent- Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, and ester waxes such as fatty acid esters and montan acid esters. The release agent is not limited to these.

[0080] As the release agent, from the viewpoints of suppressing uneven density and white voids in the obtained image and having good compatibility with the amorphous polyester resin, thereby improving the fixability of the image, an ester wax is preferred, and an ester wax of a higher fatty acid having from 10 to 30 carbon atoms and a monovalent or polyvalent alcohol component having from 1 to 30 carbon atoms is more preferred.

[0081] The ester wax is a wax having an ester bond. The ester wax may be any of a monoester, diester, triester, and tetraester, and any known natural or synthetic ester wax can be used. Examples of ester waxes include ester compounds of higher fatty acids (such as fatty acids having 10 or more carbon atoms) and monohydric or polyhydric aliphatic alcohols (such as aliphatic alcohols having 8 or more carbon atoms), and have a melting temperature of 60°C or higher and 110°C or lower (preferably 65°C or higher and 100°C or lower, more preferably 70°C or higher and 95°C or lower). Examples of ester waxes include ester compounds of higher fatty acids (caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, oleic acid, etc.) and alcohols (monohydric alcohols such as methanol, ethanol, propanol, isopropanol, butanol, capryl alcohol, lauryl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, oleyl alcohol, etc.; polyhydric alcohols such as glycerin, ethylene glycol, propylene glycol, sorbitol, pentaerythritol, etc.). Specific examples include carnauba wax, rice wax, candelilla wax, jojoba oil, Japan wax, beeswax, privet wax, lanolin, and montanic acid ester wax.

[0082] The melting temperature of the release agent is preferably 50°C or higher and 110°C or lower, and more preferably 60°C or higher and 100°C or lower. The melting temperature of the release agent is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "melting peak temperature" described in the method for determining melting temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0083] The content of the release agent is preferably from 1% by mass to 20% by mass, and more preferably from 5% by mass to 15% by mass, based on the total mass of the toner particles.

[0084] -Coloring agent- In the aggregating step, it is preferable that the dispersion liquid further contains colorant particles. Examples of colorants include carbon black, chrome yellow, Hansa Yellow, benzidine yellow, threne yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, Balkan orange, watch young red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont oil red, pyrazolone red, lithol red, rhodamine B lake, lake red C, pigment red, rose bengal, aniline blue, ultramarine blue, and tetrahydrofuran. Examples of the dyes include various pigments such as phosphorus blue, chalcoil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate, and various dyes such as acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, aniline black-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, and thiazole-based dyes. The colorant may be used alone or in combination of two or more kinds.

[0085] The colorant may be surface-treated as necessary, or may be used in combination with a dispersant. In addition, a plurality of types of colorants may be used in combination.

[0086] The content of the colorant is, for example, preferably from 1% by mass to 30% by mass, and more preferably from 3% by mass to 15% by mass, based on the total mass of the toner particles.

[0087] -Other additives- Examples of other additives include well-known additives such as magnetic materials, charge control agents, inorganic powders, etc. These additives are contained in the toner particles as internal additives.

[0088] -Characteristics of toner particles, etc.- The toner particles may be toner particles having a single layer structure, or may be toner particles having a so-called core-shell structure (core-shell type particles) composed of a core (core particle) and a coating layer (shell layer) that coats the core. The toner particles having a core-shell structure are composed of, for example, a core containing a binder resin and, if necessary, a colorant and a release agent, and the like, and a coating layer containing a binder resin. Among these, the toner particles are preferably core-shell type particles from the viewpoints of low-temperature fixability and suppression of color streaks.

[0089] Toner volume average particle size (D 50v ) is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm.

[0090] The volume average particle size of the toner is measured using a Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and the electrolyte is measured using an ISOTON-II (manufactured by Beckman Coulter, Inc.). For the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 mL of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and this is then added to 100 mL to 150 mL of the electrolyte. The electrolyte with the sample suspended in it is dispersed for 1 minute using an ultrasonic disperser, and the particle size of each particle in the range of 2 μm to 60 μm is measured using a Coulter Multisizer II with an aperture of 100 μm in diameter. The number of particles sampled is 50,000. For the measured particle size, a cumulative distribution based on volume is drawn from the smallest diameter side, and the particle size at which the cumulative 50% occurs is called the volume average particle size D 50v It is defined as:

[0091] In this embodiment, the average circularity of the toner particles is not particularly limited, but from the viewpoint of improving the cleaning properties of the toner from the image carrier, it is preferably 0.91 or more and 0.98 or less, more preferably 0.94 or more and 0.98 or less, and even more preferably 0.95 or more and 0.97 or less.

[0092] In this embodiment, the circularity of a toner particle is the perimeter of a circle having the same area as the projected image of the particle divided by the perimeter of the projected image of the particle, and the average circularity of a toner particle is the cumulative circularity of 50% from the smallest side in the distribution of circularity. The average circularity of a toner particle is determined by analyzing at least 3,000 toner particles using a flow-type particle image analyzer.

[0093] The average circularity of the toner particles can be controlled, for example, by adjusting the stirring speed of the dispersion, the temperature of the dispersion, or the retention time in the fusing step.

[0094] The amount of release agent on the toner particle surface can be controlled by, for example, adjusting the amount of release agent charged, the type of release agent, the temperature during melting and kneading, or by performing surface treatment with hot air after pulverization.

[0095] <External additives> The toner produced by the method for producing a toner for developing electrostatic images according to the present embodiment may contain an external additive, if necessary. The toner produced by the method for producing a toner for developing electrostatic images according to this embodiment may be toner particles that do not contain an external additive, or toner particles to which an external additive has been added. The external additive may be, for example, inorganic particles. The inorganic particles may be, for example, SiO 2 , TiO 2 , Al 2 O 3 , CuO, ZnO, SnO 2 , CEO 2 , Fe 2 O 3 , MgO, BaO, CaO, K 2 O, Na 2 O, ZrO 2 , CaO SiO 2 , K 2 O (TiO 2 ) n , Al 2 O 3 2SiO 2 , CaCO 3 , MgCO 3 , BaSO 4 , MgSO4 etc.

[0096] The surface of the inorganic particles as an external additive may be subjected to a hydrophobic treatment. The hydrophobic treatment may be performed, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These may be used alone or in combination of two or more. The amount of the hydrophobizing agent is preferably, for example, 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the inorganic particles.

[0097] Examples of external additives include resin particles (resin particles such as polystyrene, polymethyl methacrylate (PMMA), and melamine resin), cleaning agents (for example, metal salts of higher fatty acids such as zinc stearate, and fluorine-based polymer particles).

[0098] The amount of the external additive added is, for example, preferably from 0.01% by mass to 10% by mass, and more preferably from 0.01% by mass to 6% by mass, based on the toner particles.

[0099] <Electrostatic image developer> The electrostatic image developer according to this embodiment contains at least the toner produced by the method for producing a toner for developing electrostatic images according to this embodiment. The electrostatic image developer according to the present embodiment may be a one-component developer containing only the toner produced by the method for producing a toner for developing electrostatic images according to the present embodiment, or may be a two-component developer in which the toner is mixed with a carrier.

[0100] The carrier is not particularly limited, and may be any known carrier, such as a coated carrier in which the surface of a core material made of magnetic powder is coated with a coating resin, a magnetic powder dispersion type carrier in which magnetic powder is dispersed and mixed in a matrix resin, or a resin impregnated type carrier in which porous magnetic powder is impregnated with a resin. The magnetic powder dispersion type carrier and the resin impregnated type carrier may be a carrier in which the constituent particles of the carrier are used as a core material and are coated with a coating resin.

[0101] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt, and magnetic oxides such as ferrite and magnetite.

[0102] Examples of the coating resin and matrix resin include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylic acid ester copolymer, straight silicone resin containing an organosiloxane bond or a modified product thereof, fluororesin, polyester, polycarbonate, phenolic resin, and epoxy resin. The coating resin and the matrix resin may contain other additives such as conductive particles. Examples of the conductive particles include particles of metals such as gold, silver, and copper, carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.

[0103] Here, in order to coat the surface of the core material with a coating resin, a method of coating with a coating layer forming solution in which the coating resin and, if necessary, various additives are dissolved in an appropriate solvent can be mentioned. The solvent is not particularly limited and may be selected taking into consideration the coating resin to be used, the suitability for application, etc. Specific resin coating methods include an immersion method in which the core material is immersed in a solution for forming a coating layer, a spray method in which the solution for forming a coating layer is sprayed onto the surface of the core material, a fluidized bed method in which the solution for forming a coating layer is sprayed onto the core material while it is suspended in flowing air, and a kneader coater method in which the core material of a carrier and the solution for forming a coating layer are mixed in a kneader coater and the solvent is removed.

[0104] In the two-component developer, the mixture ratio (mass ratio) of the toner and the carrier is preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100.

[0105] <Image forming device / image forming method> An image forming apparatus / image forming method according to this embodiment will be described. The image forming apparatus according to the present embodiment includes an image carrier, a charging means for charging the surface of the image carrier, an electrostatic image forming means for forming an electrostatic image on the surface of the charged image carrier, a developing means for containing an electrostatic image developer and developing the electrostatic image formed on the surface of the image carrier as a toner image with the electrostatic image developer, a transfer means for transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing means for fixing the toner image transferred to the surface of the recording medium. The electrostatic image developer according to the present embodiment is used as the electrostatic image developer.

[0106] In the image forming apparatus according to this embodiment, an image forming method (the image forming method according to this embodiment) is carried out, which includes a charging step of charging the surface of an image carrier, an electrostatic image forming step of forming an electrostatic image on the surface of the charged image carrier, a developing step of developing the electrostatic image formed on the surface of the image carrier as a toner image using the electrostatic image developer according to this embodiment, a transfer step of transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing step of fixing the toner image transferred to the surface of the recording medium.

[0107] The image forming apparatus according to the present embodiment may be any of known image forming apparatuses, such as a direct transfer type apparatus in which a toner image formed on the surface of an image holder is directly transferred to a recording medium; an intermediate transfer type apparatus in which a toner image formed on the surface of an image holder is primarily transferred to the surface of an intermediate transfer body, and the toner image transferred to the surface of the intermediate transfer body is then secondarily transferred to the surface of a recording medium; an apparatus equipped with a cleaning means for cleaning the surface of the image holder before charging after the transfer of the toner image; and an apparatus equipped with a discharging means for irradiating the surface of the image holder with discharging light to discharge it before charging after the transfer of the toner image. Among them, an image forming apparatus equipped with a cleaning means for cleaning the surface of the image carrier is preferable, and a cleaning blade is preferable as the cleaning means. In the case of an intermediate transfer type device, the transfer means has, for example, an intermediate transfer body onto whose surface a toner image is transferred, a primary transfer means which primarily transfers the toner image formed on the surface of the image carrier onto the surface of the intermediate transfer body, and a secondary transfer means which secondarily transfers the toner image transferred onto the surface of the intermediate transfer body onto the surface of a recording medium.

[0108] In the image forming apparatus according to the present embodiment, for example, a portion including the developing means may have a cartridge structure (process cartridge) that is detachably attached to the image forming apparatus. As the process cartridge, for example, a process cartridge including a developing means that contains the electrostatic image developer according to the present embodiment is preferably used.

[0109] An example of an image forming apparatus according to the present embodiment will be described below, but the present invention is not limited to this. Note that only the main parts shown in the drawings will be described, and descriptions of the rest will be omitted.

[0110] FIG. 1 is a schematic diagram showing the configuration of an image forming apparatus according to the present embodiment. The image forming apparatus shown in Fig. 1 includes first to fourth electrophotographic image forming units 10Y, 10M, 10C, and 10K (image forming means) that output images of each color of yellow (Y), magenta (M), cyan (C), and black (K) based on color-separated image data. These image forming units (hereinafter sometimes simply referred to as "units") 10Y, 10M, 10C, and 10K are arranged in parallel at predetermined distances from each other in the horizontal direction. These units 10Y, 10M, 10C, and 10K may be process cartridges that are detachable from the image forming apparatus.

[0111] Above each of the units 10Y, 10M, 10C, and 10K in the drawing, an intermediate transfer belt 20 is provided as an intermediate transfer body extending through each unit. The intermediate transfer belt 20 is provided wound around a drive roll 22 and a support roll 24 that are arranged from left to right in the drawing at a distance from each other and contact the inner surface of the intermediate transfer belt 20, and is adapted to run in a direction from the first unit 10Y to the fourth unit 10K. Note that a force is applied to the support roll 24 in a direction away from the drive roll 22 by a spring or the like (not shown), and tension is applied to the intermediate transfer belt 20 wound around them. In addition, an intermediate transfer body cleaning device 30 is provided on the image carrier side of the intermediate transfer belt 20, facing the drive roll 22. Further, the developing devices (developing means) 4Y, 4M, 4C, and 4K of the units 10Y, 10M, 10C, and 10K are supplied with toner including four colors of toner, yellow, magenta, cyan, and black, contained in toner cartridges 8Y, 8M, 8C, and 8K, respectively.

[0112] Since the first to fourth units 10Y, 10M, 10C, and 10K have the same configuration, the first unit 10Y that forms a yellow image and is disposed upstream in the direction in which the intermediate transfer belt travels will be described here as a representative example. Note that by assigning reference numerals of magenta (M), cyan (C), and black (K) instead of yellow (Y) to parts equivalent to those of the first unit 10Y, descriptions of the second to fourth units 10M, 10C, and 10K will be omitted.

[0113] The first unit 10Y has a photoconductor 1Y that acts as an image carrier. Around the photoconductor 1Y, a charging roll (an example of a charging means) 2Y that charges the surface of the photoconductor 1Y to a predetermined potential, an exposure device (an example of an electrostatic image forming means) 3 that exposes the charged surface to a laser beam 3Y based on a color-separated image signal to form an electrostatic image, a developing device (an example of a developing means) 4Y that supplies charged toner to the electrostatic image to develop it, a primary transfer roll 5Y (an example of a primary transfer means) that transfers the developed toner image onto an intermediate transfer belt 20, and a photoconductor cleaning device (an example of a cleaning means) 6Y that removes toner remaining on the surface of the photoconductor 1Y after the primary transfer are arranged in this order. The primary transfer roll 5Y is disposed inside the intermediate transfer belt 20 and is provided at a position facing the photoconductor 1Y. Furthermore, a bias power supply (not shown) that applies a primary transfer bias is connected to each of the primary transfer rolls 5Y, 5M, 5C, and 5K. Each bias power supply varies the transfer bias applied to each primary transfer roll under the control of a control unit (not shown).

[0114] Hereinafter, an operation of forming a yellow image in first unit 10Y will be described. First, prior to operation, the surface of the photoconductor 1Y is charged to a potential of −600V to −800V by the charging roll 2Y. The photoconductor 1Y has a conductivity (for example, a volume resistivity at 20° C. of 1×10 -6 The photosensitive layer is formed by laminating a photosensitive layer on a substrate having a resistivity of Ωcm or less. This photosensitive layer is usually highly resistive (the resistance of ordinary resins), but when irradiated with a laser beam 3Y, the resistivity of the portion irradiated with the laser beam changes. A laser beam 3Y is output to the charged surface of the photoreceptor 1Y via an exposure device 3 in accordance with image data for yellow sent from a control unit (not shown). The laser beam 3Y is irradiated onto the photosensitive layer on the surface of the photoreceptor 1Y, and an electrostatic charge image of a yellow image pattern is formed on the surface of the photoreceptor 1Y.

[0115] An electrostatic image is an image formed on the surface of the photoconductor 1Y by electrostatic charging. The laser beam 3Y reduces the resistivity of the irradiated parts of the photosensitive layer, causing the charged charges on the surface of the photoconductor 1Y to flow, while the charges remain in the parts not irradiated by the laser beam 3Y. This is a so-called negative latent image. The electrostatic image formed on the photoconductor 1Y is rotated to a predetermined developing position as the photoconductor 1Y travels. Then, at this developing position, the electrostatic image on the photoconductor 1Y is made visible as a toner image (developed image) by the developing device 4Y.

[0116] The developing device 4Y contains an electrostatic image developer including at least yellow toner and a carrier, for example. The yellow toner is triboelectrically charged by being stirred inside the developing device 4Y, and is held on a developer roll (an example of a developer holder) with a charge of the same polarity (negative polarity) as the charge on the photoconductor 1Y. As the surface of the photoconductor 1Y passes through the developing device 4Y, the yellow toner electrostatically adheres to the discharged latent image portion on the surface of the photoconductor 1Y, and the latent image is developed with the yellow toner. The photoconductor 1Y on which the yellow toner image has been formed continues to travel at a predetermined speed, and the toner image developed on the photoconductor 1Y is transported to a predetermined primary transfer position.

[0117] When the yellow toner image on the photoreceptor 1Y is transported to the primary transfer, a primary transfer bias is applied to the primary transfer roll 5Y, and an electrostatic force from the photoreceptor 1Y toward the primary transfer roll 5Y acts on the toner image, and the toner image on the photoreceptor 1Y is transferred onto the intermediate transfer belt 20. The transfer bias applied at this time has a polarity (+) opposite to the polarity (-) of the toner, and in the first unit 10Y, for example, it is controlled to +10 μA by a control unit (not shown). On the other hand, the toner remaining on the photoconductor 1Y is removed and collected by the photoconductor cleaning device 6Y.

[0118] Further, the primary transfer bias applied to the primary transfer rolls 5M, 5C, and 5K subsequent to the second unit 10M is also controlled in accordance with the first unit. In this manner, the intermediate transfer belt 20 onto which the yellow toner image has been transferred by the first unit 10Y is conveyed successively through the second to fourth units 10M, 10C, and 10K, where the toner images of the respective colors are transferred in a superimposed manner.

[0119] The intermediate transfer belt 20 onto which the four color toner images have been transferred in multiple layers through the first to fourth units reaches a secondary transfer section that is composed of the intermediate transfer belt 20, a support roll 24 that contacts the inner surface of the intermediate transfer belt, and a secondary transfer roll (an example of a secondary transfer means) 26 arranged on the image bearing surface side of the intermediate transfer belt 20. Meanwhile, a recording paper (an example of a recording medium) P is fed at a predetermined timing into the gap between the secondary transfer roll 26 and the intermediate transfer belt 20 via a supply mechanism, and a secondary transfer bias is applied to the support roll 24. The transfer bias applied at this time has a (-) polarity that is the same as the (-) polarity of the toner, and an electrostatic force from the intermediate transfer belt 20 toward the recording paper P acts on the toner image, so that the toner image on the intermediate transfer belt 20 is transferred onto the recording paper P. The secondary transfer bias at this time is determined according to the resistance detected by a resistance detection means (not shown) that detects the resistance of the secondary transfer section, and is voltage-controlled.

[0120] Thereafter, the recording paper P is sent to a pressure contact portion (nip portion) of a pair of fixing rolls in a fixing device (one example of a fixing means) 28, where the toner image is fixed onto the recording paper P, forming a fixed image.

[0121] The recording paper P onto which the toner image is transferred can be, for example, plain paper used in electrophotographic copying machines, printers, etc. In addition to the recording paper P, other examples of the recording medium include overhead projector sheets, etc. To further improve the smoothness of the image surface after fixing, it is preferable that the surface of the recording paper P is also smooth. For example, coated paper in which the surface of ordinary paper is coated with resin or the like, art paper for printing, etc. are preferably used.

[0122] After the color image has been fixed, the recording paper P is conveyed toward the discharge section, and the series of color image forming operations is completed.

[0123] <Process cartridge / toner cartridge> The process cartridge according to this embodiment will be described. The process cartridge according to this embodiment is a process cartridge that contains the electrostatic image developer according to this embodiment, is equipped with a developing means that develops an electrostatic image formed on the surface of an image carrier using the electrostatic image developer into a toner image, and is detachably attached to an image forming apparatus.

[0124] In addition, the process cartridge according to this embodiment is not limited to the above configuration, and may be configured to include a developing device and, as necessary, at least one other means selected from an image carrier, a charging means, an electrostatic image forming means, and a transfer means.

[0125] An example of a process cartridge according to the present embodiment will be described below, but the present invention is not limited to this example. Note that only the main parts shown in the drawings will be described, and descriptions of the rest will be omitted.

[0126] FIG. 2 is a schematic diagram showing the process cartridge according to the present embodiment. The process cartridge 200 shown in FIG. 2 is configured by, for example, a housing 117 having a mounting rail 116 and an opening 118 for exposure, and integrally combining and holding a photoconductor 107 (an example of an image carrier), a charging roll 108 (an example of a charging means) provided around the photoconductor 107, a developing device 111 (an example of a developing means), and a photoconductor cleaning device 113 (an example of a cleaning means), which are assembled into a cartridge. In FIG. 2, 109 denotes an exposure device (an example of an electrostatic image forming means), 112 denotes a transfer device (an example of a transfer means), 115 denotes a fixing device (an example of a fixing means), and 300 denotes recording paper (an example of a recording medium).

[0127] Next, the toner cartridge according to this embodiment will be described. The toner cartridge according to the present embodiment is a toner cartridge that contains the toner according to the present embodiment and is detachably attached to an image forming apparatus. The toner cartridge contains replenishment toner to be supplied to a developing unit provided in the image forming apparatus.

[0128] 1 is an image forming apparatus having a configuration in which toner cartridges 8Y, 8M, 8C, and 8K can be attached and detached, and the developing devices 4Y, 4M, 4C, and 4K are connected to the toner cartridges corresponding to the respective developing devices (colors) through toner supply pipes (not shown). When the toner contained in the toner cartridge becomes low, the toner cartridge is replaced. EXAMPLES

[0129] Hereinafter, the present embodiment will be described in more detail with reference to examples and comparative examples, but the present embodiment is not limited to these examples. Note that "parts" and "%" indicating amounts are based on mass unless otherwise specified.

[0130] [Synthesis of polyester resin] In a reaction vessel equipped with a stirrer, a thermometer, a condenser and a nitrogen gas inlet tube, 80 mol parts of polyoxypropylene (2,2)-2,2-bis (4-hydroxyphenyl) propane, 10 mol parts of ethylene glycol, 10 mol parts of cyclohexanediol, 80 mol parts of terephthalic acid, 10 mol parts of isophthalic acid and 10 mol parts of n-dodecenyl succinic acid were charged, and the reaction vessel was replaced with dry nitrogen gas. Then, 0.25 mass parts of titanium tetrabutoxide was charged as a catalyst with respect to 100 mass parts of the monomer component. After stirring and reacting for 3 hours at 170°C under a nitrogen gas flow, the temperature was further raised to 210°C over 1 hour, the pressure in the reaction vessel was reduced to 3 kPa, and the reaction was stirred and reacted under reduced pressure for 13 hours to obtain a polyester resin. The glass transition temperature of the obtained resin was measured using a differential scanning calorimeter (DSC) and found to be 58°C.

[0131] [Preparation of Polyester Resin Particle Dispersion] The above polyester resin: 100 parts by weight Ethyl acetate: 70 parts by weight Isopropyl alcohol: 15 parts by weight The mixed solvent of the ethyl acetate and the isopropyl alcohol was put into a jacketed stainless steel vessel, and the polyester resin was gradually put therein and completely dissolved while stirring to obtain an oil phase. A 10% by mass aqueous ammonia solution was gradually dripped into the stirred oil phase by a pump so that the total amount was 3 parts by mass, and 230 parts by mass of ion-exchanged water was gradually dripped at a rate of 10 L / min to cause phase inversion emulsification. After that, a polyester resin particle dispersion (solid content concentration: 40% by mass) was obtained by performing vacuum distillation. The solid content concentration was measured using a moisture meter MA35 (manufactured by Sartorius Mechatronics Japan Co., Ltd.). The solid content concentration of each sample below was measured in the same manner. The volume average particle diameter (D50v) of the polyester resin particles in the obtained polyester resin particle dispersion was 180 nm. The volume average particle diameter of the polyester resin particles was measured using a laser diffraction particle size distribution measuring device (LA-700: manufactured by Horiba, Ltd.). The measurement method was to adjust the sample in the state of a dispersion liquid to about 2 g in solid content, add ion-exchanged water to this to make it about 40 mL, put this into a cell until the appropriate concentration was reached, wait for 2 minutes, and measure when the concentration in the cell became almost stable. The volume average particle diameters obtained for each particle size range (channel) were accumulated from the smallest volume average particle diameter, and the volume average particle diameter (D50v) was determined as the point where the accumulation reached 50%.

[0132] [Preparation of Release Agent Particle Dispersion] Paraffin wax (manufactured by Nippon Seiro Co., Ltd., FNP92, endothermic peak onset 81°C): 45 parts Anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 5 parts - Ion-exchanged water: 200 parts The above was mixed and heated to 95°C, and dispersed using a homogenizer (IKA Ultra Turrax T50). After that, it was dispersed using a Manton-Gaulin high pressure homogenizer (Gaulin) to prepare a release agent particle dispersion (solid content concentration: 20%) in which the release agent was dispersed. The volume average particle size of the release agent particles was 0.19 μm.

[0133] [Preparation of Colorant Particle Dispersion] Cyan pigment (Dainichi Seikagaku Kogyo Co., Ltd., Pigment Blue 15:3 (copper phthalocyanine)): 98 parts Anionic surfactant (Daiichi Kogyo Seiyaku Co., Ltd., Neogen R): 2 parts - Ion-exchanged water: 400 parts The above ingredients were mixed and dissolved, and dispersed for 10 minutes using a homogenizer (IKA Ultra Turrax), to obtain a colorant particle dispersion having a median particle size of 0.16 μm and a solid content of 20%.

[0134] Example 1 [Toner Preparation] Polyester resin particle dispersion: 100 parts by weight Colorant particle dispersion: 10 parts by weight Release agent particle dispersion: 9 parts by weight Ion-exchanged water: 200 parts by weight Demol SN-B aqueous solution (formalin condensate sodium sulfonate (polymer dispersant), manufactured by Kao Corporation, adjusted to a solid content of 10%): 1.3 parts by weight The raw material was put into a tank having a jacket capable of heating and cooling, and 3 parts of 0.3M (=mol / L) nitric acid aqueous solution was added to adjust the pH to 3.0. Next, while circulating through a disperser (manufactured by Pacific Machinery Works, Ltd., Cavitron) installed outside the stirring tank, 50 parts of 10% aluminum sulfate aqueous solution was dropped as a flocculant, mixed and dispersed, and heated at a jacket temperature of 50°C while stirring with a stirring blade. Then, for coating the aggregated particles, a resin particle dispersion for coating, which was prepared by mixing 25 parts of polyester resin dispersion and 10 parts of ion-exchanged water and adjusted to pH 3.0 in advance, was added and held for 10 minutes. Then, in order to stop the growth of the coated aggregated particles (adhered particles), a 1M (=mol / L) sodium hydroxide aqueous solution was added, and the pH of the raw material mixture was controlled to 8.0. Next, in order to fuse the aggregated particles, the temperature was raised to 96°C at a heating rate of 1°C / min, and after reaching 90°C, it was held for 4 hours. Thereafter, the mixture was cooled to 40° C. to obtain a toner slurry. The particle size distribution was measured using a Coulter Multisizer II (aperture diameter: 50 μm, manufactured by Coulter Corp.) The volume average particle size was 6.0 μm, and the proportion of particles with a size of 10 μm or more was 0.4% by volume. Furthermore, this toner slurry was washed and dried to obtain toner particles, and the chargeability was evaluated as described below. As a result, the charge amount under high temperature and high humidity conditions (28° C. / 85% RH) was 38 μC / g.

[0135] Example 2 [Toner Preparation] Polyester resin particle dispersion: 100 parts by weight Colorant particle dispersion: 10 parts by weight Release agent particle dispersion: 9 parts by weight Ion-exchanged water: 200 parts by weight A toner slurry was prepared in the same manner as in Example 1, except that 5.2 parts by mass of an aqueous solution of Demol SN-B (solid content rate: 10%) was added to the mixture. The particle size distribution was measured using a Coulter Multisizer II (aperture diameter: 50 μm, manufactured by Coulter Corp.) The volume average particle size was 5.9 μm, and the proportion of particles with a size of 10 μm or more was 0.3% by volume. Furthermore, this toner slurry was washed and dried to obtain toner particles, and the chargeability was evaluated as described below. As a result, the charge amount under high temperature and high humidity conditions (28° C. / 85% RH) was 29 μC / g.

[0136] Example 3 A toner slurry was obtained in the same manner as in Example 1, except that the Demol SN-B aqueous solution was changed to a Demol SC-30 aqueous solution (formalin condensate sulfonic acid sodium salt (polymer dispersant), manufactured by Kao Corporation, adjusted to a solid content of 10%). The particle size distribution was measured using a Coulter Multisizer II (aperture diameter: 50 μm, manufactured by Coulter Corp.) The volume average particle size was 5.9 μm, and the proportion of particles with a size of 10 μm or more was 0.4 volume %. Furthermore, this toner slurry was washed and dried to obtain toner particles, and the chargeability was evaluated as described below. As a result, the charge amount under high temperature and high humidity conditions (28° C. / 85% RH) was 37 μC / g.

[0137] Example 4 A toner slurry was obtained in the same manner as in Example 2, except that the Demol SN-B aqueous solution was changed to a Demol SC-30 aqueous solution (formalin condensate sulfonic acid sodium salt (polymer dispersant), manufactured by Kao Corporation, adjusted to a solid content of 10%). The particle size distribution was measured using a Coulter Multisizer II (aperture diameter: 50 μm, manufactured by Coulter Corp.) The volume average particle size was 5.9 μm, and the proportion of particles with a size of 10 μm or more was 0.3% by volume. Furthermore, this toner slurry was washed and dried to obtain toner particles, and the chargeability was evaluated as described below. As a result, the charge amount under high temperature and high humidity conditions (28° C. / 85% RH) was 28 μC / g.

[0138] Example 5 A toner slurry was obtained in the same manner as in Example 1, except that the Demol SN-B aqueous solution was changed to a Demol EP aqueous solution (sodium salt of α-olefin-maleic acid copolymer (polymer dispersant), manufactured by Kao Corporation, adjusted to a solid content of 10%). The particle size distribution was measured using a Coulter Multisizer II (aperture diameter: 50 μm, manufactured by Coulter Corp.) The volume average particle size was 6.0 μm, and the proportion of particles with a size of 10 μm or more was 0.7% by volume. Furthermore, this toner slurry was washed and dried to obtain toner particles, and the chargeability was evaluated as described below. As a result, the charge amount under high temperature and high humidity conditions (28° C. / 85% RH) was 39 μC / g.

[0139] Example 6 A toner slurry was obtained in the same manner as in Example 1, except that the Demol SN-B aqueous solution was changed to a DKS Discoat aqueous solution (ammonium salt of styrene-maleic acid copolymer (polymer dispersant), manufactured by Daiichi Kogyo Seiyaku Co., Ltd., adjusted to a solid content of 10%). The particle size distribution was measured using a Coulter Multisizer II (aperture diameter: 50 μm, manufactured by Coulter Corp.) The volume average particle size was 5.9 μm, and the proportion of particles with a size of 10 μm or more was 0.8% by volume. Furthermore, this toner slurry was washed and dried to obtain toner particles, and the chargeability was evaluated as described below. As a result, the charge amount under high temperature and high humidity conditions (28° C. / 85% RH) was 37 μC / g.

[0140] Example 7 A toner slurry was obtained in the same manner as in Example 1, except that in the preparation of the release agent particle dispersion, the release agent (manufactured by Nippon Seiro Co., Ltd., FNP92) was changed to a release agent (manufactured by Nippon Seiro Co., Ltd., HNP9). The particle size distribution was measured using a Coulter Multisizer II (aperture diameter: 50 μm, manufactured by Coulter Corp.) The volume average particle size was 5.9 μm, and the proportion of particles with a size of 10 μm or more was 0.8% by volume. Furthermore, this toner slurry was washed and dried to obtain toner particles, and the chargeability was evaluated as described below. As a result, the charge amount under high temperature and high humidity conditions (28° C. / 85% RH) was 33 μC / g.

[0141] Example 8 [Toner Preparation] Polyester resin particle dispersion: 100 parts by weight Colorant particle dispersion: 10 parts by weight Release agent particle dispersion: 9 parts by weight Ion-exchanged water: 200 parts by weight The above raw materials were put into a tank having a jacket capable of heating and cooling, and 3 parts of 0.3M (=mol / L) nitric acid aqueous solution were added to adjust the pH to 3.0. Next, while circulating through a disperser (manufactured by Pacific Machinery Works, Ltd., Cavitron) installed outside the stirring tank, 50 parts of 10% aluminum sulfate aqueous solution was dropped as a flocculant, mixed and dispersed, and then 1.3 parts by mass of Demol SN-B aqueous solution (formalin condensate sulfonic acid sodium salt (polymer dispersant), manufactured by Kao Corporation, adjusted to a solid content rate of 10%) was added, and the jacket temperature was heated at 50 ° C. while stirring with a stirring blade. Then, a resin particle dispersion for coating, which was prepared by mixing 25 parts of polyester resin dispersion and 10 parts of ion-exchanged water and adjusted to pH 3.0 in advance, was added as a coating resin particle dispersion for coating, and held for 10 minutes. Then, in order to stop the growth of the coated aggregated particles (adhered particles), a 1M (=mol / L) sodium hydroxide aqueous solution was added, and the pH of the raw material mixture was controlled to 8.0. Next, in order to fuse the aggregated particles, the temperature was increased to 96° C. at a rate of 1° C. / min, and after reaching 90° C., the temperature was maintained for 4 hours, followed by cooling to 40° C. to obtain a toner slurry. The particle size distribution was measured using a Coulter Multisizer II (aperture diameter: 50 μm, manufactured by Coulter Corp.) The volume average particle size was 6.0 μm, and the proportion of particles with a size of 10 μm or more was 0.6% by volume. Furthermore, this toner slurry was washed and dried to obtain toner particles, and the chargeability was evaluated as described below. As a result, the charge amount under high temperature and high humidity conditions (28° C. / 85% RH) was 39 μC / g.

[0142] Example 9 A toner slurry was obtained in the same manner as in Example 1, except that in the preparation of the toner, Demol SN-B was added without being made into an aqueous solution. The particle size distribution was measured using a Coulter Multisizer II (aperture diameter: 50 μm, manufactured by Coulter Corp.) The volume average particle size was 5.9 μm, and the proportion of particles with a size of 10 μm or more was 0.7% by volume. Furthermore, this toner slurry was washed and dried to obtain toner particles, and the chargeability was evaluated as described below. As a result, the charge amount under high temperature and high humidity conditions (28° C. / 85% RH) was 37 μC / g.

[0143] Comparative Example 1 [Toner Preparation] Polyester resin particle dispersion: 100 parts by weight Colorant particle dispersion: 10 parts by weight Release agent particle dispersion: 9 parts by weight Ion-exchanged water: 200 parts by weight A toner slurry was prepared in the same manner as in Example 1, except that no polymer dispersant was added. The particle size distribution was measured using a Coulter Multisizer II (aperture diameter: 50 μm, manufactured by Coulter Corp.) The volume average particle size was 5.9 μm, and the proportion of particles with a size of 10 μm or more was 2.1% by volume. Furthermore, this toner slurry was washed and dried to obtain toner particles, and the chargeability was evaluated as described below. As a result, the charge amount under high temperature and high humidity conditions (28° C. / 85% RH) was 30 μC / g.

[0144] Comparative Example 2 [Toner Preparation] Polyester resin particle dispersion: 100 parts by weight Colorant particle dispersion: 10 parts by weight Release agent particle dispersion: 9 parts by weight Ion-exchanged water: 200 parts by weight A toner slurry was prepared in the same manner as in Example 1, except that 66 parts by mass of an aqueous solution of Demol SN-B (solid content: 10%) was added to the toner. The particle size distribution was measured using a Coulter Multisizer II (aperture diameter: 50 μm, manufactured by Coulter Corp.) The volume average particle size was 5.9 μm, and the proportion of particles with a size of 10 μm or more was 0.2% by volume. Furthermore, this toner slurry was washed and dried to obtain toner particles, and the chargeability was evaluated as described below. As a result, the charge amount under high temperature and high humidity conditions (28° C. / 85% RH) was 12 μC / g.

[0145] Comparative Example 3 Polyester resin particle dispersion: 100 parts by weight Colorant particle dispersion: 10 parts by weight Release agent particle dispersion: 9 parts by weight Ion-exchanged water: 200 parts by weight The above raw materials were put into a tank having a jacket capable of heating and cooling, and 3 parts of 0.3M nitric acid aqueous solution were added to adjust the pH to 3.0. Next, while circulating through a disperser (manufactured by Pacific Machinery Works, Ltd., Cavitron) installed outside the stirring tank, 50 parts of 10% aluminum sulfate aqueous solution was dropped as a flocculant, mixed and dispersed, and then heated at a jacket temperature of 50 ° C. while stirring with a stirring blade. Then, for coating the aggregated particles, a resin particle dispersion for coating, which was prepared by mixing 25 parts of polyester resin dispersion and 10 parts of ion-exchanged water and adjusted to pH 3.0 in advance, was added and held for 10 minutes. Then, in order to stop the growth of the coated aggregated particles (adhered particles), a 1M aqueous sodium hydroxide solution was added to control the pH of the raw material mixture to 8.0. Next, 3 parts by mass of Demol SN-B aqueous solution (solid content rate 10%) was added, and the temperature was raised to 96 ° C. at a heating rate of 1 ° C. / min in order to fuse the aggregated particles, and after reaching 90 ° C., it was held for 4 hours. Thereafter, the mixture was cooled to 40° C. to obtain a toner slurry. The particle size distribution was measured using a Coulter Multisizer II (aperture diameter: 50 μm, manufactured by Coulter Corp.) The volume average particle size was 5.9 μm, and the proportion of particles with a size of 10 μm or more was 1.4 volume %. Furthermore, this toner slurry was washed and dried to obtain toner particles, and the chargeability was evaluated as described below. As a result, the charge amount under high temperature and high humidity conditions (28° C. / 85% RH) was 20 μC / g.

[0146] Comparative Example 4 A toner slurry was obtained in the same manner as in Comparative Example 2, except that the Demol SN-B aqueous solution was changed to a Demol SC-30 aqueous solution (formalin condensate sodium sulfonate (polymer dispersant), manufactured by Kao Corporation, adjusted to a solid content of 10%). The particle size distribution was measured using a Coulter Multisizer II (aperture diameter: 50 μm, manufactured by Coulter Corp.) The volume average particle size was 6.0 μm, and the proportion of particles with a size of 10 μm or more was 0.2% by volume. Furthermore, this toner slurry was washed and dried to obtain toner particles, and the chargeability was evaluated as described below. As a result, the charge amount under high temperature and high humidity conditions (28° C. / 85% RH) was 11 μC / g.

[0147] Comparative Example 5 A toner slurry was obtained in the same manner as in Comparative Example 3, except that the Demol SN-B aqueous solution was changed to a Demol SN-B aqueous solution (formalin condensate sulfonic acid sodium salt (polymer dispersant), manufactured by Kao Corporation, adjusted to a solid content of 10%). The particle size distribution was measured using a Coulter Multisizer II (aperture diameter: 50 μm, manufactured by Coulter Corp.) The volume average particle size was 6.0 μm, and the proportion of particles with a size of 10 μm or more was 1.4 volume %. Furthermore, this toner slurry was washed and dried to obtain toner particles, and the chargeability was evaluated as described below. As a result, the charge amount under high temperature and high humidity conditions (28° C. / 85% RH) was 22 μC / g.

[0148] Comparative Example 6 A toner slurry was obtained in the same manner as in Comparative Example 2, except that the DEMOL SN-B aqueous solution was changed to a NEOGEN R aqueous solution (sodium alkylbenzene sulfonate (surfactant), manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.). The particle size distribution was measured using a Coulter Multisizer II (aperture diameter: 50 μm, manufactured by Coulter Corp.) The volume average particle size was 5.9 μm, and the proportion of particles with a size of 10 μm or more was 1.1% by volume. Furthermore, this toner slurry was washed and dried to obtain toner particles, and the chargeability was evaluated as described below. As a result, the charge amount under high temperature and high humidity conditions (28° C. / 85% RH) was 12 μC / g.

[0149] <Evaluation of coarse powder suppression> A Coulter Multisizer-II (manufactured by Beckman Coulter) was used as the measuring device, and ISOTON-II (manufactured by Beckman Coulter) was used as the electrolyte. In the measuring method, 0.5 mg of the measurement sample was added to 2 mL of a 5% aqueous solution of a surfactant (sodium dodecylbenzenesulfonate) as a dispersant, and this was added to 100 mL of the electrolyte to prepare an electrolyte in which the measurement sample was suspended. The electrolyte in which the measurement sample was suspended was dispersed for about 1 minute using an ultrasonic disperser, and the particle size distribution of particles with a particle size range of 2.0 to 60 μm was measured using the Coulter Multisizer-II with an aperture with an aperture diameter of 50 μm. The number of particles measured was 50,000. The measured particle size distribution was drawn as a cumulative distribution from the small diameter side for the divided particle size range (channel) in terms of volume, and the particle size at which the cumulative 50% was obtained was defined as D50v. The proportion of coarse particles after fusion was evaluated according to the following criteria. The practical acceptable range is A or B. A: The volume ratio of particles 10 μm or larger is less than 0.5% by volume B: The volume ratio of particles of 10 μm or more is 0.5 volume% or more and less than 1.0 volume% C: Particle volume ratio of 10 μm or more is 1.0 volume% or more but less than 2.0 volume% D: Particle volume ratio of 10 μm or more is less than 2.0 volume%

[0150] <Evaluation of electrostatic charge in high temperature and high humidity environments> One part of colloidal silica (R972, manufactured by Nippon Aerosil Co., Ltd.) was externally added to 100 parts of the obtained toner particles, and the mixture was mixed using a Henschel mixer to obtain a toner for developing electrostatic images. 100 parts of ferrite particles (manufactured by Powder Tech Co., Ltd., average particle size 50 μm) and 1 part of polymethyl methacrylate resin (manufactured by Mitsubishi Rayon Co., Ltd., weight average molecular weight 95,000) were placed in a pressure kneader together with 500 parts of toluene and mixed at room temperature (25° C.) for 15 minutes. The mixture was then heated to 70° C. while mixing under reduced pressure, the toluene was distilled off, and the mixture was cooled and sized using a 105 μm sieve to produce a ferrite carrier (resin-coated carrier). This ferrite carrier was mixed with the above-mentioned toner for developing electrostatic images to prepare a two-component electrostatic image developer having a toner concentration of 7% by weight. The obtained electrostatic image developer was filled into a developing device and seasoned for 24 hours under a high temperature and high humidity environment (28°C / 85%RH). After that, the developing device was idled for 3 minutes under the same environment, and the charge amount of the developer under high temperature and high humidity (initial charge amount) was measured using a blow-off charge amount measuring device (TB200, manufactured by Toshiba Corporation). The amount of charge was evaluated according to the following criteria. The practical acceptable range is A or B. A: 35μC / g or more B: 25μC / g or more and less than 35μC / g C: 15μC / g or more and less than 25μC / g D: Less than 15μC / g

[0151] The evaluation results are summarized in Table 1.

[0152] [Table 1]

[0153] From the above results, it is understood that in this embodiment, compared with the comparative example, the generation of coarse powder during production is small, and a toner for developing electrostatic images having excellent charging properties under a high temperature and high humidity environment can be obtained. [Explanation of symbols]

[0154] 1Y, 1M, 1C, 1K Photoconductor (an example of an image carrier) 2Y, 2M, 2C, 2K Charging roll (an example of a charging means) 3 Exposure device (an example of an electrostatic image forming means) 3Y, 3M, 3C, 3K laser beam 4Y, 4M, 4C, 4K developing device (an example of developing means) 5Y, 5M, 5C, 5K Primary transfer roll (an example of a primary transfer means) 6Y, 6M, 6C, 6K Photoconductor cleaning device (an example of a cleaning means) 8Y, 8M, 8C, 8K toner cartridges 10Y, 10M, 10C, 10K Image forming units 20 Intermediate transfer belt (an example of an intermediate transfer body) 22 Driving Roll 24 Support roll 26 Secondary transfer roll (an example of a secondary transfer means) 30 Intermediate transfer body cleaning device 107 Photoconductor (an example of an image carrier) 108 Charging roll (an example of charging means) 109 Exposure device (an example of electrostatic image forming means) 111 Developing device (an example of developing means) 112 Transfer device (an example of a transfer means) 113 Photoconductor cleaning device (an example of a cleaning means) 115 Fixing device (an example of fixing means) 116 Mounting Rail 118 Exposure Aperture 117 Cabinet 200 Process Cartridge 300 Recording paper (an example of a recording medium) P Recording paper (an example of a recording medium)

Claims

1. an aggregation step of aggregating at least the binder resin particles and the release agent particles contained in the dispersion to form aggregated particles; a fusing step of heating and fusing the aggregated particles to form fused particles; and a washing step of filtering and washing the fused particles to obtain toner particles. Before or during the aggregation step, a polymer dispersant is added to the dispersion in an amount of 0.01% by mass or more and 1.3% by mass or less based on the total mass of the toner particles to be obtained. In the aggregating step, the solid content concentration of the dispersion is 11% by mass or more and 20% by mass or less. A method for producing a toner for developing electrostatic images.

2. 2. The method for producing a toner for developing electrostatic images according to claim 1, wherein the polymer dispersant is at least one compound selected from the group consisting of formalin condensate sulfonate, a salt of an α-olefin-maleic acid copolymer, and a salt of a styrene-maleic acid copolymer.

3. 3. The method for producing a toner for developing electrostatic images according to claim 2, wherein the polymer dispersant is a formalin condensate sulfonate.

4. 4. The method for producing a toner for developing an electrostatic image according to claim 1, wherein the polymer dispersant is added to the dispersion liquid in an amount of 0.03% by mass or more and 1.3% by mass or less, based on the total mass of the toner particles to be obtained, before or during the aggregation step.

5. 5. The method for producing a toner for developing an electrostatic image according to claim 4, wherein the polymer dispersant is added to the dispersion liquid in an amount of 0.05% by mass or more and 1.0% by mass or less, based on the total mass of the toner particles to be obtained, before or during the aggregation step.

6. 6. The method for producing a toner for developing an electrostatic image according to claim 1, wherein the polymer dispersant is added as an aqueous solution of the polymer dispersant before or during the aggregating step.

7. 7. The method for producing a toner for developing an electrostatic image according to claim 6, wherein the polymer dispersant is added as an aqueous solution having a concentration of 1% by mass to 40% by mass of the polymer dispersant before or during the aggregating step.

8. The method for producing a toner for developing electrostatic images according to claim 1, wherein the pH of the dispersion liquid is adjusted to be acidic in the aggregation process.

9. A method for producing a toner for developing electrostatic images as described in claim 8, wherein in the aggregation process, the pH of the dispersion liquid is adjusted to 2 or more and 5 or less.

Citation Information

Patent Citations

  • Method for producing toner for developing electrostatic charge image

    JP2008209460A

  • Method of manufacturing toner for electrostatic charge image development

    JP2008304874A

  • Toner for electrostatic charge image development, developer for electrostatic charge image development, toner cartridge, process cartridge, method for producing toner for electrostatic charge image development, and image forming apparatus

    JP2012208219A

  • Stirring device and manufacturing method of agglomerated particle

    JP2019028158A